KOMPETENCJA RÓŻNOJĘZYCZNA W POCZĄTKOWYM KSZTAŁCENIU NAUCZYCIELI - Szymankiewicz, Krystyna; Kucharczyk, Radosław (Neofilolog, 2019)
Modern language policy in Europe has put forward the concept of multilingualism, and with this plurilingual competence. The definitions of both phenomena can be found in numerous documents of the Council of Europe, especially in the Common European Framework of Reference for Languages. The authors of this document describe multilingual communication in some detail, where the native speaker user is beyond the scale. A lot of attention is currently being given to issues of multilingualism in education, with numerous articles, suggestions for teaching activities and tools to develop related skills. This article raises the question of the preparation of future teachers of languages which will be taught as the second foreign language (L3) and how plurilingual competence can be developed in the classroom. The study, conducted among students of Romance languages answers the following questions. Are students, who are future L3 language teachers, adequately prepared to develop plurilingual competence in their students? Do they have the appropriate knowledge and practical skills to do this? What are their beliefs regarding the role of different languages when teaching the L3 target language?